Comparison of the properties of colorless polyimide nanocomposites containing saponite or organically modified hectorite. (April 2016) - Ju, Jieun; Chang, Jin-Hae
Poly(amic acid) (PAA) was prepared by the reaction of 4, 4′-(hexafluoro isopropylidene) diphthalic anhydride with 2, 2′-bis(trifluoromethyl) benzidine in N, N -dimethylacetamide. Hybrid films were obtained from blended solutions of the precursor polymer and saponite (SPT) or organically modified hectorite (STN) clays, and the clay content was varied from 0 to 40 wt%. The cast film of PAA was heat treated at different temperatures to create polyimide (PI) hybrid films. The nanostructure of the hybrid films was observed using transmission electron microscopy, which showed that the clay layers were well dispersed into the matrix polymer, although some clusters or agglomerated particles were also detected. The addition of SPT was more effective than the addition of STN with regard to improving the thermal properties, whereas the addition of STN was more effective with regard to improving the optical transparency and gas barrier characteristics of the PI matrix.